Efficacy of resource objective wildfires for restoration of ponderosa pine (Pinus ponderosa) forests in northern Arizona - Huffman, David W.; Sánchez Meador, Andrew J.; Stoddard, Michael T.; Crouse, Joseph E.; Roccaforte, John P. (Forest ecology and management, 2017)
•Are resource objective wildfires effective for restoring ponderosa pine forests?•Ten large fires were dominated by unburned/low and low burn severity classes.•Moderate burn severity met 67% of the restoration objectives studied.•Overall, resource objective wildfires have been 42% effective for restoration. Current conditions in dry forests of the western United State have given rise to policy mandates for accelerated ecological restoration on U.S. National Forest System and other public lands. In southwestern ponderosa pine (Pinus ponderosa Laws.) forests, mechanized tree thinning and prescribed fire are common restoration treatments but are not acceptable for all sites. Currently there is much interest in managing naturally ignited fires to accomplish restoration objectives but few studies have systematically examined the efficacy of such “resource objective” wildfires for restoring historical ranges of variability (HRV). In this study we used field plots to retrospectively sample 10 resource objective fires on two national forests in northern Arizona. We used four burn severity classes identified on Monitoring Trends in Burn Severity (MTBS) maps to stratify field sampling and compared post-fire means for 12 structure and hazardous fuels attributes to HRV and guidelines for ecosystem management. Results indicated significant differences among burn severity classes in tree density, basal area, coarse wood loads, canopy cover, and canopy fuel loads. Furthermore, areas classified as moderate (M) burn severity met HRV ranges for more attributes (67%) than did other areas in other severity classes. High (H) severity areas were within HRV for the fewest (17%) of the 12 attributes. Restoration ranges for large snag density, tree patch density and maximum patch size, and tree diameter distribution were not met within any burn severity class. Resource objective fire landscapes were comprised mainly (85%) of areas classified as unburned/low (U/L) and low (L) burn severity, whereas the M severity class made up just 12% of fire landscapes on average. Overall effectiveness of resource objective fires for meeting restoration objectives was 42%. Results suggested that effectiveness may be increased by managing for proportionally more moderate burn severity on these landscapes. For this, managers will be required to accept greater risk in terms of escaped fires and high-severity fire, which, in turn, will necessitate increasing public awareness of the potential benefits and limitations of managing wildfires for restoring ponderosa pine forest ecosystems.